2001
DOI: 10.1352/0895-8017(2001)106<0297:roritl>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Religion in the Lives of Latino Families of Young Children With Developmental Delays

Abstract: We interviewed 250 parents of Mexican and Puerto Rican origin living in the United States who had young children with developmental delays to determine the role of religion in their lives. Quantitative results indicate that parents largely viewed themselves as religious, were affiliated with a formal religion, and participated in religious activities. Most parents viewed both church and faith as supportive, but faith was shown to provide more support. Repeated measures a analysis of variance found some intragr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 35 publications
5
60
0
4
Order By: Relevance
“…These findings are mirrored in another study conducted by Skinner, Correa, Skinner, and Bailey (2001), who found that Hispanic parents believed that their child's disability was either a punishment or a gift from God. Those who believed it was a punishment thought that they were being castigated for sins they had committed.…”
Section: Hispanic Conceptions Of Disabilitysupporting
confidence: 52%
“…These findings are mirrored in another study conducted by Skinner, Correa, Skinner, and Bailey (2001), who found that Hispanic parents believed that their child's disability was either a punishment or a gift from God. Those who believed it was a punishment thought that they were being castigated for sins they had committed.…”
Section: Hispanic Conceptions Of Disabilitysupporting
confidence: 52%
“…Research has shown that cultural and religious beliefs play an important role in how family members interpret and understand disability (e.g., Jegatheesan, 2005;Jegatheesan, Miller, & Fowler, 2010;Shaked, 2005;Skinner, Correa, Skinner, & Bailey, 2001). Such beliefs inform parents on issues such as childrearing and socialization practices, as well as expectations and roles of other family members such as siblings.…”
Section: Implications and Recommendations For Future Researchmentioning
confidence: 99%
“…Dating back to the Spanish conquest of Mexico and Central and South America, religion has shaped the worldviews of people living in Latin American for over 500 years. As such, religion has become an integral part of Latin American culture providing both spiritual and practical aid (Skinner, Correa, Skinner, Baily, 2001). Studies have revealed that religion is used for assistance, support, socialization and has historically provided hope and meaning to Latinos during difficult life circumstances (Espinosa, Virgilio, & Miranda, 2003;Skinner et al, 2001).…”
Section: Religion In the Latino Culturementioning
confidence: 99%
“…(p. 18) Among Latinos in the U.S., religious traditions are connected with family, friends, and even folk healers (Skinner et al, 2001). Religious ceremonies are considered social events, which strengthen bonds among family and friends as well as extended support systems (Gonzalez-Morkos, 2005).…”
Section: Religion In the Latino Culturementioning
confidence: 99%
See 1 more Smart Citation